Virtual team experiences in an emerging economy: a qualitative study. Issue 4 (27th June 2018) - Gupta, Shubhi; Pathak, Govind Swaroop
Abstract : Purpose: The purpose of this paper is to document the experiences of team members in order to map the kinds of experiential outcomes that they report while working in virtual teams. The study will help to expand the understanding of various issues related to virtual work arrangements from the perceptions of information technology (IT) professionals in India. Design/methodology/approach: The study was conducted by adopting an exploratory approach with the use of qualitative methodology. The method of sampling adopted was purposive cum snowball sampling. Semi-structured interviews (face-to-face and telephonic) were conducted by taking a sample of 52 respondents, who are employed by IT organisations. The interviews were recorded digitally, transcribed and analysed by using the content-coding approach followed by a thematic analysis. Findings: The foremost contribution of the study is that it has considered the various motivators and the skills required to be a successful virtual team player. Significant challenges encountered in virtual teams have also been identified. Practical implications: Virtual teams in the contemporary business environment are evolving with an unparalleled velocity. The findings of the paper have implications for managers, team leaders and change agents regarding how to transform and sustain in the rapidly changing business context of emerging economies. Originality/value: In the extant literature on virtual teams very little is known about how individual members perceive this new form of teamwork. The findings of the study advance research on the topic of virtual teams by lending empirical support with respect to the interaction effects between IT and human beings. Recommendations have been provided for individual team members and organisations.